The economics of patient safety in primary and ambulatory care Flying blind - Auraaen, Ane (OECD Health Working Papers, 2018)
Building on published patient safety research literature, this paper aims to broaden the existing knowledge base on safety lapses occurring in primary and ambulatory care settings. The findings of this paper show that safety lapses in primary and ambulatory care are common. About half of the global burden of patient harm originates in primary and ambulatory care, and estimates suggest that nearly four out of ten patients experience safety issue(s) in their interaction with this setting. Safety lapses in primary and ambulatory care most often result in an increased need for care or hospitalisations. Available evidence estimates the direct costs of safety lapses - the additional tests, treatments and health care - in primary and ambulatory care to be around 2.5% of total health expenditure. Safety lapses resulting in hospitalisations each year may count 6% of total hospital bed days and more than 7 million admissions in the OECD.